2016 IEEE/AIAA 35th Digital Avionics Systems Conference (DASC) 2016
DOI: 10.1109/dasc.2016.7777995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pilot feedback regarding the use of state awareness technologies during complex situations

Abstract: A flight simulation study was conducted at NASA Langley Research Center to evaluate flight deck systems that (1) predict aircraft energy state and/or autoflight configuration, (2) present the current state and expected future state of automated systems, and/or (3) show the state of flight-critical data systems in use by automated systems and primary flight instruments. Four new technology concepts were evaluated vis-à-vis current state-of-the-art flight deck systems and indicators. This human-in-the-loop study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The following sub-sections provide selected evidence supporting these hypotheses and claims. Additional results can be found in [9] [10]. In some areas, data analyses continue and will be published in future reports.…”
Section: Selected Findingsmentioning
confidence: 90%
See 4 more Smart Citations
“…The following sub-sections provide selected evidence supporting these hypotheses and claims. Additional results can be found in [9] [10]. In some areas, data analyses continue and will be published in future reports.…”
Section: Selected Findingsmentioning
confidence: 90%
“…Below, these four technologies are briefly explained. Additional descriptions of their designs for this study, and findings resulting from their use can be found in [9] and [10].…”
Section: A Technologies Under Evaluationmentioning
confidence: 99%
See 3 more Smart Citations